Analisis Penentuan Harga Pokok Penjualan Sepatu Thrift Singapura by Lix - Serenade, Vincensia; Ulfa, Mutia; Lailiyah, Nita Ilmiyatul; Mardiani, Novita (Jurnal Informatika Ekonomi Bisnis, 2023)
This research focuses on applying the Cost of Goods Sold (HPP) to determine the selling price of UMKM Thrift Shoes Singapore by Lix in Padang City. Using production cost data for the sales price of men's and women's shoes in 2022. The owner still does not know how to calculate a good cost of goods sold, this is evidenced by the lack of knowledge of the MSME owner of Thrift Shoes Singapore by Lix regarding proper management of cost of goods sold. In addition, the MSME owner of Thrift Shoes Singapore by Lix uses the cost of goods sold as the selling price without increasing profit margins.